MICROSATELLITE BASED GENETIC DIVERSITY IN INDIGENOUS GOAT BREEDS REARED IN ALGERIA AND TURKEY - H. Tefiel; N. Ata; K. Fantazi; O. Yilmaz; I. Cemal; O. Karaca; M. Chahbar; A. Ameur Ameur; S. B. S. Gaouar (Journal of Animal and Plant Sciences, 2020)
In the present study, the relationship between some indigenous goat breeds from Algeria (Arbia (AR), Mekatia (ME), Naine de Kabylie (NK) and M’zabite (MO)) and Turkey (Hair goat (HG) and Damascus (DA)) was investigated with 18 microsatellites markers recommended by FAO (2011). Three multiplex groups were formed according to fragment length of microsatellites. Polymerase chain reaction (PCR) amplifications were carried out in 25-μL total volumes. Touchdown PCR protocols was used for amplification of specific genomic regions. Capillary electrophoresis was used for the separation of the PCR fragments labeled with fluorescent dye in the Beckman Coulter GeXP genetic analyzer. PIC, FIS, FIT and FST values were 0.93, 0.083, 0.146 and 0.069, respectively. The Ho and He values estimated as 0.81 and 0.93, respectively. The MNA across the breeds ranged from 12.78 in the MO to 15.72 in the AR breed. The Ho ranged from 0.77 (DA breed) to 0.88 (NK breed). The He is lowest in HG breed (0.84) and highest in NK breed (0.90). All breeds showed positive FIS values. The private alleles observed in the studied goat breeds were highest (33) in the DA breed, with a total of 117 private alleles. However, only 58 of them had a frequency higher than 5%. As a result, the dendrogram shows that the Algerian goat breeds were completely separated from the Turkish goat breed. On the other hand, ΔK value indicated that the most suitable group number was 3 (K=3). Further studies are recommended considering goats from other Mediterranean countries.
Keywords: Genetic diversity; Algerian goat breeds; Turkish goat breeds; microsatellites; population genetic structure